PENGARUH KEPARAHAN MALOKLUSI TERHADAP PERSEPSI ESTETIKA ORAL (Tinjauan pada Siswa SMA/Sederajat di Kawasan Non-Perkotaan Banjarmasin) - Alya Nurrasyifa Maharani; Irnamanda D.H; Aulia Azizah; Isnur Hatta; Amy Nindia Carabelly (Dentin, 2026)
Background: Malocclusion is one of the oral health problems with a relatively high prevalence in Indonesia. This condition not only affects oral cavity function but also has an impact on facial aesthetics and the psychosocial aspects of adolescents. The severity of malocclusion can be assessed using the Index of Complexity, Outcome, and Need (ICON), while the perception of oral aesthetics can be measured through a self-perception questionnaire. Objective: To determine the effect of malocclusion severity on oral aesthetic perception among senior high school/equivalent students in the non-urban area of Banjarmasin. Methods: This study used an analytical observational design with a cross-sectional approach. The study sample consisted of 175 senior high school/equivalent students selected by simple random sampling. Data on malocclusion severity were obtained from jaw impressions measured using the ICON index, while data on oral aesthetic perception were collected through a questionnaire. Data analysis was performed using the Spearman correlation test with a statistical application program. Results: The majority of students had mild (31.4%) and very mild (28.6%) levels of malocclusion severity, while severe and very severe categories were found in (11.4%) and (13.7%) of students, respectively. Most respondents had a positive oral aesthetic perception (57.1%). The correlation coefficient value was 0.571, indicating that the malocclusion severity variable affected oral aesthetic perception by 57.1% with a moderate strength of effect, while the remaining percentage was influenced by other factors. The positive direction of the effect means that the higher the level of malocclusion severity, the more negative the students’ oral aesthetic perception. Conclusion: There is a significant effect between malocclusion severity and oral aesthetic perception among senior high school/equivalent students in the non-urban area of Banjarmasin. This indicates the importance of paying attention to malocclusion not only from functional aspects but also from the aesthetic and psychosocial aspects of adolescents.Keywords: ICON, Malocclusion, Oral Aesthetic Perception